Religious Experience and the Transformation of Narcissism: Kohutian Theory and the Life of St. Francis of Assisi - Cataldo, Lisa M. (Journal of religion and health, 2007)
Kohut proposed that the narcissistic personality could be transformed in the therapeutic environment by an empathic approach on the part of the analyst. Within the analytic setting, specific transference phenomena arise spontaneously, allowing the analysand to confront infantile grandiose fantasies and unresolved narcissistic wounds. Using the story of the life of St. Francis of Assisi, this paper illustrates how religious experience--specifically the ongoing encounter with a transcendent other--can provide the "therapeutic" milieu in which the mirroring, idealizing, and twinship transferences described by Kohut can arise, and within which pathological narcissism can be transformed into the "cosmic narcissism" of the healthy personality.